An Island of Stability: Art Images and Natural Scenes – but Not Natural Faces – Show Consistent Esthetic Response in Alzheimer’s-Related Dementia - Graham, Daniel; Stockinger, Simone; Leder, Helmut (Frontiers in Psychology, 2013)
Alzheimer’s disease causes severe impairments in cognitive function but there is evidence that aspects of aesthetic perception are somewhat spared, at least in early stages of the disease. People with early Alzheimer’s-related dementia have been found to show similar degrees of stability over time in aesthetic judgment of paintings compared to controls, despite poor explicit memory for the images. Here we expand on this line of inquiry to investigate the types of perceptual judgments involved, and to test whether people in later stages of the disease also show evidence of preserved aesthetic judgment. Our results confirm that, compared to healthy controls, there is similar aesthetic stability in early stage Alzheimer’s disease (AD) in the absence of explicit memory, and we report here that people with later stages of the disease also show similar stability compared to controls. However, while we find that stability for portrait paintings, landscape paintings, and landscape photographs is not different compared to control group performance, stability for face photographs—which were matched for identity with the portrait paintings—was significantly impaired in the AD group. We suggest that partially spared face-processing systems interfere with aesthetic processing of natural faces in ways that are not found for artistic images and landscape photographs. Thus, our work provides a novel form of evidence regarding face processing in healthy and diseased ageing. Our work also gives insights into general theories of aesthetics, since people with Alzheimer’s disease are not encumbered by many of the semantic and emotional factors that otherwise color aesthetic judgment. We conclude that, for people with Alzheimer’s disease, basic aesthetic judgment of artistic images represents an “island of stability” in a condition that in most other respects causes profound cognitive disruption. As such, aesthetic response could be a promising route to future therapies.